The Current Approach to Male Patients with Lower Urinary TractSymptoms - (:unkn) unknown (My University, 2021)
Objective: The goal of this study was to investigate the current daily approach of urologists for the initial evaluation of men with lower urinarytract symptoms (LUTS) in accordance with the European Association of Urology (EAU) guidelines.Materials and Methods: An online survey was used to identify the daily practices of urologists for men over the age of 45 with LUTS. Based onthe EAU guidelines, an 11-item questionnaire was created. A link to the SurveyMonkey questionnaire was sent to members of a national urologyassociation along with an e-mail message. Moreover, the data were analysed after collecting all of the responses.Results: Out of 1.182 urologists who received an invitation message, 166 (14.04%) responded and completed the questionnaire. The mean age of theurologists who responded was 42.24+10.11. More than half of the participants (56.6%) work at centres that have a urology residency programme.Furthermore, the most commonly performed laboratory test in men with LUTS was urinalysis. Approximately 90% of urologists performed urinalysis.In addition, 84% of participants routinely measured prostate-specific antigen in every man between the ages of 45 and 75. In all men withLUTS, approximately half of the urologists routinely used renal function tests, urinary ultrasonography, post-void residual urine measurement,uroflowmetry, and symptom score assessment. For men with nocturia and/or storage phase symptoms, the majority of participants (69.9%) useda bladder diary. Moreover, urologists who worked at university hospitals were found to use bladder diaries significantly more frequently in theirclinical practice (p=0.037).Conclusion: We discovered that there was no clinical approach standard among urologists for men with LUTS